Peningkatan Hasil Belajar Pendidikan Agama Kristen Dengan Metode Bermain Peran Di SMP Negeri 1 Sunggal - Melfi Siburian (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
The objectives of this study are (1) to improve PAK learning outcomes by applying the role playing learning method to Class 9-1 students of SMP Negeri 1 Sunggal for the 2020/2021 academic year, (2) to improve. This research is classroom action research with 2 cycles, each cycle consists of 4 activities, namely planning, action, observation and reflection followed by planning in the next cycle by utilizing the results of previous reflections. The solution design in question is an action in the form of a role-playing learning method in teaching the subject of Church self-renewal Class 9-1, 9-3 Class 9-1 SMP Negeri 1 Sunggal for the academic year 2020/2021 as many as 31 people. The findings of the study indicate that PAK learning with role playing learning methods can improve student learning outcomes as evidenced by the increase in PAK learning outcomes in each cycle, from an average of 70.52 to an average of 80.19. students feel happy learning PAK and are motivated to learn This implies that by applying the role playing learning method (role playing) can improve teacher skills, student activities or positive responses to the learning, for that teachers are expected to apply and develop play learning methods role (role playing) in PAK learning.